2006
DOI: 10.1093/toxsci/kfj177
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reactivity, Cytotoxic, and Morphological Transforming Effects of Diatomaceous Earth Products in Syrian Hamster Embryo Cells

Abstract: In order to evaluate the effect of thermal treatments on the surface reactivity and carcinogenic potential of diatomaceous earth (DE) products, the physicochemical features of some specimens--derived by heating the same original material--were compared with their cytotoxic and transforming potency. The samples were an untreated DE (amorphous) progressively heated in the laboratory at 900 degrees C (DE 900) and 1200 degrees C (DE 1200) and a commercial product manufactured from the same DE (Chd) from which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 25 publications
9
27
0
2
Order By: Relevance
“…In our study, concentrations of 3.8 to 15.2 µg/cm 2 induced similar TF (0.24-0.71%) to that shown by Hesterberg and Barrett [21], and the crystallized silica was again found to be less potent than the asbestos (0.28 % TF with 1.91 µg/cm 2 of chrysotile vs. 0.4 % TF with 30.4 µg/ cm 2 of Chd or 0.24% TF with 3.81 µg/ cm 2 of Min-U-Sil). All of these data are in agreement with the previously reported data [18].…”
Section: The She Cell Transformation Assay Which Uses Primary Cell Csupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, concentrations of 3.8 to 15.2 µg/cm 2 induced similar TF (0.24-0.71%) to that shown by Hesterberg and Barrett [21], and the crystallized silica was again found to be less potent than the asbestos (0.28 % TF with 1.91 µg/cm 2 of chrysotile vs. 0.4 % TF with 30.4 µg/ cm 2 of Chd or 0.24% TF with 3.81 µg/ cm 2 of Min-U-Sil). All of these data are in agreement with the previously reported data [18].…”
Section: The She Cell Transformation Assay Which Uses Primary Cell Csupporting
confidence: 93%
“…In the present work, we have shown that crystallized silica (Chd and Min-U-Sil) was able to induce transformed SHE colonies in a dose-dependent manner after seven days of treatment. Our results are in agreement with previous transformation studies on quartz [18], [21], [22], [23] and [24]. Hesterberg and Barrett [21] showed that two quartz samples induced a concentration-dependent increase in TF, and both of these samples were less potent than asbestos fibres.…”
Section: The She Cell Transformation Assay Which Uses Primary Cell Csupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the suitability of the Bhas 42 CTA for particle-type substances was assessed using crystalline (quartz Min-U-Sil 5) and amorphous (diatomaceous earth) silica microparticles that have been previously evaluated for their transforming activity in the Syrian hamster embryonic (SHE) CTA [17,18]. [19] (Table 1).…”
Section: Introductionmentioning
confidence: 99%